2010
DOI: 10.1140/epjb/e2010-00255-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the one-dimensional quantum compass model

Abstract: The ground state magnetic phase diagram of the one-dimensional quantum compass model (QCM) is studied using the numerical Lanczos method. A detailed numerical analysis of the low energy excitation spectrum is presented. The energy gap and the spin-spin correlation functions are calculated for finite chains. Two kind of the magnetic long-range orders, the Néel and a type of the stripe-antiferromagnet, in the ground state phase diagram are identified. Based on the numerical analysis, the first and second order q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 21 publications
3
37
0
Order By: Relevance
“…[10] and [15]. They have shown that the first-order transition occurs at multicritical point where a line of first-order transition (J 1 /L 1 = 0) meets with a line of second order transition (J 2 /L 1 = 1).…”
Section: Phase Diagrammentioning
confidence: 99%
“…[10] and [15]. They have shown that the first-order transition occurs at multicritical point where a line of first-order transition (J 1 /L 1 = 0) meets with a line of second order transition (J 2 /L 1 = 1).…”
Section: Phase Diagrammentioning
confidence: 99%
“…The ground state of the QC model is known to be in the gapped Neel phase in the region (J 1 > 0, J 2 < 1) [19]. To study the induced effects of the NNN interaction on the magnetic behavior of the ground state we did a very accurate simulation and the results are presented in Fig.…”
Section: Frustrated Compass Modelmentioning
confidence: 99%
“…The ground state phase diagram of the model is very rich including four different gapped phases which are separated with the first-order (J 1 /L = 0) and the second-order (J 2 /L = 1) critical lines [5,6]. The point where the line of the first-order transition (J 1 /L = 0) meets with a line of the second-order (J 2 /L = 1) transition is called the multicritical point.…”
Section: Correlation Functions At the Multicritical Pointmentioning
confidence: 99%
“…In particular, we consider the 1D spin-1/2 quantum compass model [1][2][3][4][5][6][7]. In fact, the quantum compass model is defined for explaining the low-temperature behavior of some Mott insulators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation